2017
DOI: 10.1038/mp.2016.198
|View full text |Cite
|
Sign up to set email alerts
|

ASD and schizophrenia show distinct developmental profiles in common genetic overlap with population-based social communication difficulties

Abstract: Difficulties in social communication are part of the phenotypic overlap between autism spectrum disorders (ASD) and schizophrenia. Both conditions follow, however, distinct developmental patterns. Symptoms of ASD typically occur during early childhood, whereas most symptoms characteristic of schizophrenia do not appear before early adulthood. We investigated whether overlap in common genetic influences between these clinical conditions and impairments in social communication depends on the developmental stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
122
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(141 citation statements)
references
References 54 publications
15
122
4
Order By: Relevance
“…Another key question is whether the SCDC‐measured traits we observed in adolescent girls are truly autistic in nature, or whether they represent a different type of social impairment, for example, arising from the onset of internalising problems, ADHD or psychosis risk (St Pourcain, Eaves, et al., ; St Pourcain, Robinson et al., ). Several strands of evidence support the notion that the female social variability we observed in adolescence is related to autism.…”
Section: Discussionmentioning
confidence: 97%
“…Another key question is whether the SCDC‐measured traits we observed in adolescent girls are truly autistic in nature, or whether they represent a different type of social impairment, for example, arising from the onset of internalising problems, ADHD or psychosis risk (St Pourcain, Eaves, et al., ; St Pourcain, Robinson et al., ). Several strands of evidence support the notion that the female social variability we observed in adolescence is related to autism.…”
Section: Discussionmentioning
confidence: 97%
“…Here, we extend previous work relating participation and polygenic risk for schizophrenia and autism in ALSPAC 13 , 14 by: (i) investigating polygenic scores for other factors which could influence participation in the ALSPAC mothers and children; (ii) investigating the potential impact of selection bias by comparing associations between genetic factors and measured phenotypes in the largest sample with genetic data and a more selected subsample; and (iii) conducting genome-wide association studies of participation measures.…”
Section: Introductionmentioning
confidence: 90%
“…A number of studies have used a polygenic risk score or similar approaches to show overlap in common genetic variation between schizophrenia and developmental outcomes in the general population, and have shown that alleles which increase risk for schizophrenia also associate with, for example, poorer cognitive function and impaired social and communication difficulties, similar to those seen in people with autism spectrum disorders. While the overlaps are not large, neither are they trivial (genetic correlations between 0.18 and 0.37) and support the involvement of alleles that increase risk for schizophrenia in a wider set of developmental traits.…”
Section: Comparative Genetic Architecture Of Schizophrenia and Other mentioning
confidence: 99%